Perancangan Ui/Ux Aplikasi Bank Sampah Guna Monitoring Program Pengelolaan Sampah Desa Saringembat Menggunakan - Nihayah, Alfiyatu; Audytra, Hastie; Rokhim, Auliyaur (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2025)
The problems faced by the village garbage bank are related to unstructured waste management, which includes several aspects such as lack of public participation, lack of awareness of the importance of garbages management, and lack of efficiency in data management. UCD is a design design method that places the user at the heart of the design development process. Usability Testing is an evaluation method applied in user experience design to test a product or service with a real user. This process involves the user directly in testing the product or services to assess the level of ease of use, intuitiveness of interaction, and end user satisfaction.Based on the questionnaire that has been tested, it indicates that the system usability scale test has been carried out on the UI/UX designs that have been created and obtained a score of 86 which means that the score falls in the category Very Good with grade scale A, or in terms of usability based on the data that the application has been made obtains a rating that is acceptable or worthy of use by the community.